Merit Pay: Increase or Hinder Performance? - sofyandi, Herman (International Journal of Psychosocial Rehabilitation, 2020)
Organizations or companies implement the merit system solely to improve the performance of their employees. This is because the reward system stimulates the motivation of work to improve their performance. Although merit pay is widely used by many organizations, in fact some businesses still question whether merit pay can improve employee and organizational performance. At present, merit pay is still a contradiction. This article tries to understand the pros and cons of the implementation of merit pay as well as its positive and negative aspects. The final part of this article tries to understand how merit pay must be implemented by the organization to make it more effective.